Discusión crítica entre el arte contemporáneo y el contexto social de la ciudad de Machala. - Astudillo Leon, Fausto Teodoro (2017)
The present research work on the Critical Discourse between Contemporary Art and the Social Context of the City of Machala corresponds to an analysis that aims to question and highlight social problems, which are very important to analyze them through an investigation to later express it artistically Through new techniques, which characterizes contemporary art. The artistic expression gives us the possibility of claiming and changing the misconception that society has regarding the ignorance of art and that it is only for a specific audience. Contemporary aesthetics have transformed this way of thinking of the collective, art becomes public and tries to have the viewer intervene in the proposal. The research aims to reconsider, make society aware of the issue of abortion and value the life that is the most fundamental. In contemporary societies this class of situations is considered as a criminal act, therefore even though educational institutions are taught as sexual subjects, these atrocious acts are still committed. It also shows the positive and negative of technology, the positive is a bibliographic resource that brings knowledge, the negative is the increase in promiscuity and debauchery, which brings unwanted pregnancy and ends in the practice of a Abortion; In which adolescence is the most vulnerable group. From the artistic field it is somehow to arrive with the message and to achieve a significant change in the city.